High rates of potentially infectious exposures between immunocompromised patients and their companion animals: an unmet need for education. Issue 3 (March 2017) - Gurry, Greta A.; Campion, Veronique; Premawardena, Chamath; Woolley, Ian; Shortt, Jake; Bowden, Donald K.; Kaplan, Zane; Dendle, Claire
Abstract : A cross‐sectional survey of 265 adult patients with haematological malignancy, haemoglobinopathy or human immunodeficiency virus was performed to determine the potential risk of infection from animal exposures. One hundred and thirty‐seven (52%) owned an animal; the majority were dogs (74%) and cats (39%), but 14% owned birds and 3% reptiles. Eighty percent engaged in behaviour with their animals that potentially put them at risk of zoonotic infections. The most frequent behaviours were picking up animal faeces 72 (52%), cleaning animal areas 69 (50%) and allowing animals to sleep in the same bed 51 (37%). Twenty‐eight percent allowed the animal to lick their face. Of all patients, 80 (30%) had been bitten or scratched by an animal. Only 16% of those who owned pets could recall receiving education regarding safe behaviours around animals. These immunocompromised patients are at risk of infection through exposure to pets. Our study highlights the need for increased education of patients regarding how to remain safe around their pets.